Pengalaman Guru dalam Menerapkan Metode Ceramah: Studi Fenomenologis Berbasis Wawancara - Kholidah Nur; Fitti Nurhaliza; Putri Damayanti; Rizki Anggina; Febriyanti Damayanti; Muhammad Hatta (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study aims to describe educators’ experiences when using the lecture method through a phenomenological interview-based approach. The primary objective of this research is to explore teachers’ perspectives, strategies, challenges, and meanings behind their experiences in applying the lecture method during teaching activities. Data were collected through in‑depth interviews with several teachers representing diverse teaching backgrounds. The findings indicate that the lecture method is still considered effective for delivering certain learning materials that require direct explanation. However, teachers face several challenges such as students’ lack of attention, limited time, and pressure to diversify instructional methods. Nevertheless, teachers strive to optimize the lecture method by combining it with visual media, questioning techniques, and relevant examples to make learning more interactive. This study concludes that teachers’ experiences in using the lecture method are strongly influenced by classroom context, student characteristics, and teachers’ creativity in adjusting instructional strategies.